Polymorphism of MC4R gene associated with feed intake, nutrient digestibility, ADG and FCR at post-weaning in Bligon goats - Latifah, L.; Maharani, D.; Kustantinah, K.; Hartatik, T. (Diponegoro University, 2020)
The melanocortin-4 receptor (MC4R) gene plays an important role in sympathetic nerve activity, as well as adrenal and thyroid function and mediates the effects of leptin on energy homeostasis. This study aimed to investigate the effect of the 642 bpMC4R gene on feed intake, nutrient digestibility, average daily gain (ADG),and feed conversion ratio (FCR)at post-weaned in Bligon goat. Forty-six Bligon were used for the blood sample collection, and genomic DNA was extracted using the Geneaid isolation kit. Feed intake data were collected on 46 Bligon goats kept on 2 different animal houses, including the laboratory’s farm of Faculty of Animal Science Universitas Gadjah Mada (FAS UGM) with n=23 and Banyusoco farm (n=23). Variables observed were feed intake, nutrient digestibility,ADG,and FCR. All samples were genotyped using the PCR-RFLP method with the KpnIenzyme. One SNP was located in the exonic region (g.1079C/T). The t-test analysis revealed a significant association between SNP g.1079C/T and the digestibility of dry matter (DM), organic matter (OM),and total digestible nutrient (TDN) of Bligon goats at 7 months of age kept on FAS UGM, as well as the digestibility of DM, crude protein (CP), nitrogen-free extract (NFE),and TDN of Bligon goats at 7 months of age kept on Banyusoco. In conclusion, it is possible to use SNP g.1079C/T for animal genotyping and asaMAS for nutrient digestibility in Bligon goats